Unlocking the condoms: The effect on sales and theft - Ashwood D; Farris KB; Campo S; Aquilino ML; Losch M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Community pharmacies may place condoms in locked displays or behind glass, thereby reducing access and consequent use.Objective: Quantify sales and theft of condoms when condoms were unlocked and removed from behind glass in grocery pharmaciesMethods: Design. In this pilot study, condom displays were unlocked in selected pharmacies for three months. Participants. Eight grocery pharmacies in central Iowa agreed to participate. Intervention. Stores provided inventory at baseline, sales/theft thereafter in three monthly reports and sales for the same period one-year earlier. Outcome measures. Descriptive statistics quantified condom theft and sales. Number of pharmacies leaving condoms unlocked after the intervention was determined.Results: Theft varied by pharmacy and ranged from an average of 1.33 boxes (units) per month to 27.33 per month. All stores experienced some increase in sales during the intervention. Two locations decided to re-lock their displays, only one indicated theft as the reason.Conclusion: After removing condoms from locked displays, more condoms were purchased and stolen from the study pharmacies. Sales outweighed theft in all pharmacies.